Trade-related employment for women in industry and services in developing countries - Susan Joekes (United Nations Research Institute for Social Development (UNRISD), 1995)
In preparation for the Fourth World Conference on Women, which was held in Beijing in September 1995, UNRISD initiated an Occasional Paper Series reflecting work carried out under the UNRISD/UNDP project, Technical Co-operation and Women's Lives: Integrating Gender into Development Policy. This paper is intended to contribute to the project's policy dialogues. It considers current changes in the international economic context as they affect the evolution of employment structures, and analyses their implications for women's employment in the trade-related manufacturing and services sectors.
Keywords: 330